PERAN PERPUSTAKAAN SEKOLAH DALAM MENINGKATKAN LITERASI INFORMASI BAGI SISWA DI SDN 03 BANYUASIN III - Rusianah , Elva (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effect of work discipline and work ability on employee performance at the Bitung City Fisheries Service. The urgency of this research lies in the urgent need to scientifically understand how two important variables of work discipline and work ability affect the performance of local government apparatus. In the era of bureaucratic reform, improving the quality of public services is a national agenda supported by the policy of evaluating the performance of the state civil apparatus (ASN) based on the merit system. The phenomenon of decreased productivity, delayed completion of tasks, and declining quality of public services are the background of the importance of this study. With a quantitative approach and survey method of 40 respondents, the data were analyzed using multiple linear regression. The results show that both work discipline and work ability have a positive and significant effect on employee performance. This study contributes to strengthening human resource governance in the public sector, especially in designing policies to improve the competence and discipline of regional apparatus.